Soil microbial load modulation improves plant–microbe interactions and bioinoculant efficacy in pathogen-stressed soils - Andargie, Yohannes Ebabuye; Lee, GyuDae; Kim, Min-Ji; Fentie, Eskindir Getachew; Jeong, Minsoo; Tagele, Setu Bazie; Lim, Kyeongmo; Azizoglu, Ugur; Shin, Jae-Ho (Frontiers in Plant Science, 2025)
Plants establish a close association with a community of microbes naturally living in the soil, known as resident soil microbiome, which typically maintains a dynamic equilibrium that confers resilience against biotic and abiotic perturbations. However, this microbiome can also reduce the success of adding new helpful microbes (bioinoculants) by reducing their functional integration with the host plant. Although bioinoculants often perform well under controlled conditions, their efficacy in pathogenic soils is frequently compromised even after repeated applications. While several factors influencing inoculation success have been examined, the impact of soil microbial load, its dynamics, and associated transcriptomic consequences remain largely overlooked. To address this gap, we induced dysbiosis in the resident soil microbiome using moist heat treatment (MHT) thereby generating a gradient in microbial load. We then assessed the phenotypic and transcriptomic responses of Cucumis sativus L., for bioinoculants alongside relative and quantitative rhizosphere microbiome profiling. MHT reduced resident soil bacterial abundance by 96.4% ± 0.9%, with 78% recovery observed after planting. This recolonization promoted plant growth and overall health by restructuring the rhizosphere microbiome and activating plant-microbe interaction pathways such as sugar metabolism, nitrogen metabolism, and aromatic compound degradation. In contrast, moist heat untreated (native) rhizosphere, with a microbial load threefold higher, resisted restructuring, favoring metabolic pathways that preserve microbial stability, such as cell wall and signal molecule biosynthesis, at the expense of plant health. Transcriptomic analyses revealed that, in moist heat treated (dysbiotic) soil conditions, bioagent inoculation triggered induced systemic resistance in cucumber, characterized by downregulation of PAL and POX gene families together with SAMDC, and upregulation of auxin-regulatory and calcium uniporter genes. This response reflected a reallocation of metabolic energy from defense to growth, while maintaining active signaling for beneficial colonization and pathogen perception via modulation of calcium influx. Our findings highlight microbial load modulation as a key strategy to facilitate rhizosphere remodeling, enhance bioinoculant efficacy, and promote plant transcriptomic responses.